(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Anemia is regarded as public health challenge and is predominant in developing countries due to nutritional deficiencies. Aim/Objectives: The study was carried out to evaluate the biological properties of Ficus capensis fruits and vegetables on some haematological parameters in 2, 4 (dinitrophenyl hydrazine) induced anemic rat. Materials and Methods: Ficus capensis leaves and fruits were separately plucked, sorted cleaned. Twenty male adult rats were purchased from the Department of Veterinary Pathology, University of Nigeria, Nsukka. The animals were divided into 4 groups of 5 rats each on the basis of body weight. The rats in all the groups received 2, 4-DNPH (20 mg/kg body weight) once daily for 7 days to induce anaemia. Group I were fed rat chow alone, group 2 were fed rat chow with ferrous sulphate, group 3 were fed rat chow with Ficus capensis leaves extract and group 4 were fed rat Ficus . The aqueous were for haematinic effects in albino rats. Blood parameters such as Packed Cell Volume (PCV), Red Blood Cell (RBC) count, White Blood Cell (WBC) count and Haemoglobin concentration (Hb) were measured. Results: The result showed that the mean PCV baseline of the rats were (38.72-39.24%), mean PCV of anemic rats (33.01- 34.60%) and the mean PCV of the rats after test of recovery were group 1 (34.10%), group 2 (51.81%), group 3 (40.20%) and group 4 (38.20%).The result showed that the mean HB baseline of the rats were (9.67-10.47 g/dl), mean HB of anemic rats (6.50- 7.10 g/dl) and the mean HB of the rats after test of recovery were group 1 (6.51 g/dl), group 2 (12.32 g/dl), group 3 (9.73 g/dl) and group 4 (9.69 g/dl). The results of the effect of the extracts on the haematological parameters indicated that oral administration of the aqueous extract of Ficus capensis leaves and fruits after 22 days exhibited a significant (P < 0.05) increase in haematinic activity by increasing the blood parameters Hb, PCV, WBC and RBC.